2018
DOI: 10.21767/2471-8505.100114
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation during ECMO: The Past, Present and Future

Abstract: In recent years, many medical centres started to use extracorporeal membrane oxygenator (ECMO) support as the last treatment option for critically ill patients when the conventional therapy fails. There are significant improvements in ECMO management since the early days of its application. In this report, we aimed to review several aspects in this complex treatment modality. One of the main areas reviewed in this article will be the anticoagulation strategy used during ECMO support and the tests utilized for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 16 publications
(17 reference statements)
1
14
0
Order By: Relevance
“…Indeed, coatings with NO-catalytic bioactivity can inhibit collagen-induced platelet activation and adhesion, proliferation, and migration of arterial smooth muscle cells through the cGMP signaling pathways. Studies showed good anti-thrombogenic properties in extracorporeal circuits [ 61 , 72 ]. Moreover, stents implanted in rabbits with this coating showed improved endothelial mimetic microenvironment, stronger recovery to the endothelium, and had less restenosis and thrombosis after 4 weeks [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, coatings with NO-catalytic bioactivity can inhibit collagen-induced platelet activation and adhesion, proliferation, and migration of arterial smooth muscle cells through the cGMP signaling pathways. Studies showed good anti-thrombogenic properties in extracorporeal circuits [ 61 , 72 ]. Moreover, stents implanted in rabbits with this coating showed improved endothelial mimetic microenvironment, stronger recovery to the endothelium, and had less restenosis and thrombosis after 4 weeks [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…The main disadvantage with NO is the fact that its storage cannot exceed 4 weeks. This can be a problem in long-term ECLS runs [ 61 , 72 ]. So far, NO-coatings have not been used commercially.…”
Section: Resultsmentioning
confidence: 99%
“…The white powder of the purified product was obtained by washing the solids with 20 mL anhydrous THF (×3) and 20 mL DEE (×1) and drying under reduced pressure (yield 27 g, 82%). The structural analysis of the product was performed by 1 H NMR recorded on a Bruker Avance III-300 FT-NMR spectrometer (Bruker Corporation, Billerica, MA, USA) at 300 MHz using deuterium oxide as a solvent. 1 2.2.3 Synthesis of p(HPMA-co-CBMAA) microgels.…”
Section: Papermentioning
confidence: 99%
“…The structural analysis of the product was performed by 1 H NMR recorded on a Bruker Avance III-300 FT-NMR spectrometer (Bruker Corporation, Billerica, MA, USA) at 300 MHz using deuterium oxide as a solvent. 1 2.2.3 Synthesis of p(HPMA-co-CBMAA) microgels. The microgels were prepared via an inverse miniemulsion polymerization using N,N′-methylenebis(acrylamide) (MBAA) crosslinker.…”
Section: Papermentioning
confidence: 99%
See 1 more Smart Citation